Satisfaction with the most recent pueiperium and factors influencing it among low risk mothers in Hulu Langat, 1996 - Rohana Ismail,; Khadijah Shamsuddin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was conducted in March 1996 to assess mothers' level of satisfaction experienced during their most recent puerperium and the factors influencing it. A total of 211 mothers who attended the Government Health Clinics in Hulu Langat was chosen for this study. The results showed that 30.3% of respondents experienced high satisfaction of their most recent puerperal experience. However,32.3% of the respondents reported having some problems during this period. The most .common problem faced by respondents with problems during puerperium were breast engorgements (35% of all reported problems among mothers) and 67.7% of their babies 67.7% had jaundice. In addition, about 11% of respondents reported being stressed during this period. The results also showed that compared to only 38.2% working respondents among those with low level of satisfaction, 50.8% of respondents with high level of satisfaction were working. High level of satisfaction was reported by respondents who were Malays and l11dians, primiparous, married 5 years, having higher education and having total family income of > RM 2000. However, the association between these factors and level of satisfaction were not statistically significant except for respondents' ethnicity. The results of this study also showed that there was a statistically significant association between level of satisfaction and social support. This study also showed that among working respondents, 66.7% felt that their maternity leaves should be longer and this was repo11ed more by respondents who were working in public sectors compared to those in private sectors. In conclusion, only 30.3% of respondents reported high level of satisfaction with their most recent puerperium. SUppO11S from closed relatives and spouse should be given to mothers to improve their level of satisfaction with their puerperal experience.